ANALISIS PENGARUH KETERSEDIAAN BAHAN BAKU KAYU UNTUK INDUSTRI MEBEL TERHADAP KONDISI EKONOMI DAN LINGKUNGAN MASYARAKAT KELURAHAN KAHURIPAN KECAMATAN TAWANG KOTA TASIKMALAYA - Pebriansah, Mohammad Apit (JURNAL GEOGRAFI, 2024)
Wood is a major commodity in an effort to advance the economic sector. Many economic sectors rely on wood as the primary raw material for production. But as time passed, the tree as the source of the wood itself began to decrease and its spread was widening. The forest as an area for planting trees has begun to decrease due to its exploitation and the presence of land transfer functions. The furniture industry is proof of how influential the availability of wood raw materials as the primary commodity for production is. It can't be stolen even though innovation continues when the metal, metal, pipe industry has begun to enter the world of furniture. But the need for wood for the furniture industry is not completely wiped out. This led to a fairly fierce competition between the wood and metal furniture industry. The main focus on the qualitative research this time relates to the impact of availability of wood raw materials on the economy and the environment at Noenoeng Tisnasaputra No.5, Kahuripan, Kec. Tawang, Kota. Tasikmalaya, West Java or better known as the Sindanggalih area. Availability of wood raw materials has become very important because many people are working in this furniture sector, some are business owners and some are working for the owners of the furniture business themselves. This makes his influence also very great on the economic sector of his society. With a wide-ranging influence on the economy and the environment, the availability of timber raw materials must remain, be vigilant, and be sustainable. The efforts of the forest conservation process as the primary source of industry became crucial, when the forests awakened the sustainability of their habitat slowly tightened due to the presence of functions, or not replant what has been cut, the wooden furniture industry is threatened even there will be a domino effect on the economy and the environment. The skill in wood processing must be mastered in order to make maximum use of it. The number of nearby furniture has created competition against the sales process, these entrepreneurs must always innovate following the pattern of the times. There is therefore a need for ways and efforts to a synergistic coexistence between forests, the environment, and the economy in society's lives . Keywords : furniture industry, business competitors, wood distribution.